Biological aspects and conservation status of the geometric tortoise, Psammobates geometricus (Linnaeus, 1758) (Cryptodira: Testudinidae) - Baard, Ernst H. W.(Ernst Hendrik Wolfaardt) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1990.